A new line list for the A2Σ+−X2Π electronic transition of OH. (September 2018) - Yousefi, Mahdi; Bernath, Peter F.; Hodges, James; Masseron, Thomas
Highlights: Calculated line list for OH A 2 Σ + − X 2 Π transition for v′=0-4 and v″=0-9. New ab initio A-X transition dipole moment. Validation with astronomical spectra. Abstract: A new line list for the A 2 Σ + − X 2 Π electronic transition of OH has been calculated. Line positions have been taken from the literature and refitted with Western's PGOPHER program. Line intensities were calculated using a new ab initio Transition Dipole Moment Function (TDMF) obtained with Molpro 2012. The new TDMF and the potential functions from LeRoy's RKR program have been used as input to LeRoy's LEVEL program in order to calculate Transition Dipole Moment Matrix Elements (TDMMEs). These matrix elements were transformed from Hund's case (b) to Hund's case (a) as required for the PGOPHER program using the method of Brooke et al. [JQSRT 2016; 168: 142–157] The line list was calculated with PGOPHER for bands with v ′ = 0 − 4 in the A 2 Σ + state and v ″ = 0 − 9 for the X 2 Π state.